Trends and inequalities in modern contraceptive use among women in Sierra Leone, 2008–2019 - Augustus Osborne; Camilla Bangura; Bright Opoku Ahinkorah (Reproductive Health)
Abstract Background Despite the known benefits of modern contraceptives in preventing unwanted pregnancies and reducing unsafe abortions, their use remains low among women of reproductive age in several sub-Saharan African countries, including Sierra Leone. This study investigated the inequalities in modern contraceptive use among women in Sierra Leone based on data from 2008 to 2019. Methods We used data from the Sierra Leone Demographic Health Survey data rounds (2008, 2013, and 2019). The World Health Organization's Health Equity Assessment Toolkit (WHO's HEAT) software was used to calculate both simple measures; Difference (D) and Ratio (R) and complex measures of inequality: Population Attributable Risk (PAR) and Population Attributable Fraction (PAF). The inequality assessment was done for five stratifiers: age, economic status, level of education, place of residence, and sub-national province. Results The study found that the prevalence of modern contraceptive use among women in Sierra Leone increased from 6.7% in 2008 to 20.9% in 2019. There was an increase in age-related inequality from a Difference of 5.9 percentage points in 2008 to 7.0 percentage points in 2019. PAF decreased from 5.7% in 2008 to 1.6% in 2019, indicating that the national average of modern contraceptive use would have increased by 5.7% in 2008 and 1.6% in 2019 in the absence of age-related inequalities. For economic status, the Difference decreased from 14.9 percentage points in 2008 to 9.9 percentage points in 2019. PAF decreased from 166.3% in 2008 to 23.3% in 2019, indicating that the national average of modern contraceptive use would have increased by 166.3% in 2008 and 23.3% in 2019 in the absence of economic-related inequalities. For education, the Difference decreased from 15.1 percentage points in 2008 to 12.4 percentage points in 2019. The PAF shows that the national average of modern contraceptive use would have reduced from 189.8%  in 2008 to 39.5% in 2019, in the absence of education-related inequality. With respect to place of residence, the Difference decreased from 10.4 percentage points in 2008 to 7.6 percentage points in 2019, and PAF decreased from 111.2% in 2008 to 23.0% in 2019. The decline in PAF indicates that the national average of modern contraceptive use would have increased by 111.2% in 2008 and 23.0% in 2019 without residence-related inequality. Provincial-related inequality decreased from a Difference of 15.5% in 2008 to 8.5% in 2019. The PAF results showed a decrease in inequality from 176.3% in 2008 to 16.7% in 2019, indicating that province would contribute 176.3% and 16.7% in 2008 and 2019 respectively to the national average of modern contraceptive use. Conclusion The use of modern contraceptives among women of reproductive age in Sierra Leone increased between 2008 and 2019 reflecting positive progress in reproductive health initiatives and access to family planning resources. The reductions in inequalities related to economic status, education, residence, and province indicate that efforts to promote equity in contraceptive access are yielding results, although age-related inequalities persist. To build on these advancements, it is recommended that policymakers continue to strengthen educational campaigns and healthcare services, particularly targeting younger women. Additionally, enhancing access to contraceptive methods through community-based programs and addressing socio-economic barriers will be crucial in further reducing inequalities and improving overall reproductive health outcomes in Sierra Leone.